Does Regulation matter? Institutional dimension of the 2008 financial crisis - Mykletun, Erik (2010)
Why did house prices fall in 2007‐2009? This is the fundamental question to most Americans, and to those who lent them money. Most homeowners did not care why residential real estate prices rose. They assumed prices always rose, and they should simply enjoy their good fortune. It was not until prices began to fall that people were left searching for answers. How much did regulation or lack thereof play in the role of the devastation? To what degree did greed and unrealistic consumer expectation have on the real estate bubble? Using existing literature as well as face to face interviews of experienced leaders within the real estate industry in California who experienced both the up and down of the real estate cycle, the overarching purpose of this study is to investigate the opinions and beliefs of the leaders and drivers within the real estate industry about the cause of the real estate bubble that occurred sharply in 2008 . Specifically, this project will focus on the opinions of real estate industry leaders who worked in the center of the subprime universe located in Irvine, California, during 2004‐2008. Comparing the mainstream beliefs with the interviewees it is fair to say that the main finding in the mainstream beliefs are reflected very well with the finding of the subject’s opinion. The thesis is divided into 6 chapters starting with 'introduction', followed by chapter 2 'Literature Review'. Chapter 3 is 'Research Methodology' followed by chapter 4 'Data Presentation'. Finally, the results are discussed in chapter 5 'Analysis and Discussion' and conclusions in Chapter 6.